2021
DOI: 10.1111/wbm.12233
|View full text |Cite
|
Sign up to set email alerts
|

Seed germination dynamics of silverleaf nightshade (Solanum elaeagnifolium Cav.) and implications for effective weed management

Abstract: Silverleaf nightshade (Solanum elaeagnifolium Cav.) is a noxious weed that threatens agricultural productivity and biodiversity worldwide. The long‐term management of soil seedbanks along with the aboveground populations of silverleaf nightshade has the potential to effectively control the species in its introduced range. Implementation of this strategy requires insights into the germination behavior of the weed in response to various environmental stimuli and endogenous cues. We assessed the morphology and ge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(14 citation statements)
references
References 32 publications
0
14
0
Order By: Relevance
“…The species is at dormancy during winter. Seed germination is favored under alternating temperatures over 20 °C, 23 while seed traits are strongly affected by the environment to which the plant is adapted 24 . It has spines in the stem and the flowers are purple, white or blue‐colored 25 .…”
Section: Integrated Management Of Important Ips: Two Case‐studiesmentioning
confidence: 99%
“…The species is at dormancy during winter. Seed germination is favored under alternating temperatures over 20 °C, 23 while seed traits are strongly affected by the environment to which the plant is adapted 24 . It has spines in the stem and the flowers are purple, white or blue‐colored 25 .…”
Section: Integrated Management Of Important Ips: Two Case‐studiesmentioning
confidence: 99%
“…Each growing season, an individual S. elaeagnifolium plant can produce in excess of 200 berries, each containing between 24 and 150 seeds (Boyd & Murray, 1982; Cuthbertson et al, 1976; Stanton et al, 2012; Utah, 2007). These seeds have been observed to vary in colour, shape and size between disconnected populations (e.g., agricultural fields, native rangelands and urban areas), and may be a result of different environmental factors such as light, nutrient availability and water, which may influence their development (Turner et al, 2021). These berries can also significantly aid in the long‐distance dispersal of S. elaeagnifolium seeds across the landscape as they can be spread via the process of animals (zoochory), human‐induced actions, water (hydrochory), and wind (anemochory) (Boyd & Murray, 1982; Cuthbertson et al, 1976; McKenzie, 1980).…”
Section: Biology and Ecologymentioning
confidence: 99%
“…The germination of S. elaeagnifolium seeds can occur in both light and dark conditions (Stanton et al, 2009), although this process requires diurnally fluctuating temperatures, a feature which has also been observed in several Solanum species (Boyd & Murray, 1982; Stanton et al, 2012). Solanum elaeagnifolium seeds are also required to be broken from physical dormancy before germination, which can be alleviated by alternating diurnal temperatures, chemical scarification or prolonged water immersion (Rutherford, 1978; Stanton et al, 2012; Turner et al, 2021). An ex situ study on S. elaeagnifolium in Texas found that seed germination is reduced when exposed to abscisic acid and salt treatments (Turner et al, 2021).…”
Section: Biology and Ecologymentioning
confidence: 99%
See 2 more Smart Citations